Peran Pendidikan Orang Tua dalam Upaya Mencegah Perjudian Online di Kalangan Remaja (Studi Kasus di Dusun Yoso Makmur Raman Aji Lampung Timur) - Hilwiatul Ahla; Irhamudin; Dedi Setiawan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
This research discusses the role of parental education in efforts to prevent gambling behaviour among teenagers aged 15-17 years and the causes of teenagers gambling online in Yoso Makmur Hamlet. Parents have a role in the personal growth and development of a child, being fully responsible for guiding and educating their children. Due to the impact of the speed of technological development, many teenagers commit deviations in the form of gambling games online. This research aims to explore the role of parental education in preventing adolescent online gambling behaviour. This research method uses a qualitative approach, and data collection uses interview, observation, and documentation techniques. The results of the analysis show that open communication, building decision-making skills, active supervision and providing an understanding of the risks of online gambling are the keys to effective parent education in preventing teenage online gambling.